2006
DOI: 10.1126/science.1128232
|View full text |Cite
|
Sign up to set email alerts
|

PirB Restricts Ocular-Dominance Plasticity in Visual Cortex

Abstract: Experience can alter synaptic connectivity throughout life, but the degree of plasticity present at each age is regulated by mechanisms that remain largely unknown. Here, we demonstrate that Paired-immunoglobulin-like receptor B (PirB), a major histocompatibility complex class I (MHCI) receptor, is expressed in subsets of neurons throughout the brain. Neuronal PirB protein is associated with synapses and forms complexes with the phosphatases Shp-1 and Shp-2. Soluble PirB fusion protein binds to cortical neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
386
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(407 citation statements)
references
References 39 publications
16
386
0
5
Order By: Relevance
“…Previous studies have shown that absence of the Nogo-66 receptor or PirB extends ODP into adulthood (20)(21)(22). However, for Nogo-66, it needs to be tested whether it is the juvenile form and whether PirB plays a role in the adult form of ODP (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that absence of the Nogo-66 receptor or PirB extends ODP into adulthood (20)(21)(22). However, for Nogo-66, it needs to be tested whether it is the juvenile form and whether PirB plays a role in the adult form of ODP (22).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the developmental increase of local inhibition appears to be the dominating mechanism to regulate cortical plasticity and CPs (15)(16)(17). Additionally, extracellular matrix remodeling is involved, as well as receptors of immune signaling, such as paired Ig-like receptor B (PirB), or axon pathfinding, such as Nogo (18)(19)(20)(21). However, a specific function to directly regulate synapse remodeling during initial neural network optimization is not known and a potential instructive function of PirB was described for adult cortical plasticity but not plasticity of the initial synapse remodeling during CPs (22).…”
mentioning
confidence: 99%
“…Diffuse synapse loss with altered cortical connectivity, as well as diffuse neuron and axon loss, are all commonly found in MS tissue 28, 29, 30, 31, 32, 33, 34, 60, 61, 62, 63 and could be driven by somatic or axonal MHC I expression. For example, neuronal MHC I has an established role in neuronal plasticity16 via mechanisms involving postsynaptic interactions with glutamate receptors and presynaptic interactions with the immunoreceptor tyrosine‐based inhibitory motif‐containing leukocyte immunoglobulin‐like receptor PirB 64. Neuronal MHC I has also been shown to inhibit glutamatergic receptor function in hippocampal circuits65 and studies in the retinogeniculate system indicate a role for somatic MHC class I in synapse elimination 66, 67.…”
Section: Discussionmentioning
confidence: 99%
“…To explore this issue, we measured the expression of Arc, an immediate early gene that is rapidly expressed in visual cortical neurons after brief visual stimulation (11,(29)(30)(31) with in situ hybridization. The visually induced expression pattern of Arc is a sensitive indicator of OD plasticity in both mice and cats (11,(29)(30)(31). As expected, after monocular enucleation (ME) in control, the functional representation of the NDE increased in control (Fig.…”
Section: Resultsmentioning
confidence: 99%